High fat diet accelerates and exacerbates microgliosis and neuronal damage/death in the somatosensory cortex after transient forebrain ischemia in gerbils - Seo, Won Joo (Lab Anim Res, 2020)
Obesity has been known as an independent risk factor for stroke. Effects of high-fat diet (HFD)-induced obesity on neuronal damage in the somatosensory cortex of animal models of cerebral ischemia have not been studied yet. In this study, HFD-induced obesity was used to study the impact of obesity on neuronal damage/loss and microgliosis in the somatosensory cortex of a gerbil model of 5-min transient forebrain ischemia. We used gerbils fed normal diet (ND) and HFD and chronologically examined microgliosis (microglial cell activation) by ionized calcium-binding adapter molecule 1 (Iba-1) immunohistochemistry. In addition, we examined neuronal damage or death by using neuronal nuclear protein (NeuN, a neuronal marker) immunohistochemistry and Fluoro-Jade B (F-J B, a marker for neuronal degeneration) histofluorescence staining. We found that ischemia-induced microgliosis in ND-fed gerbils was increased from 2 days post-ischemia; however, ischemia-mediated microgliosis in HFD-fed gerbils increased from 1 day post-ischemia and more accelerated with time than that in the ND-fed gerbils. Ischemia-induced neuronal death/loss in the somatosensory cortex in the ND-fed gerbils was apparently found at 5 days post-ischemia. However, in the HFD-fed gerbils, neuronal death/loss was shown from 2 days post-ischemia and progressively exacerbated at 5 days post-ischemia. Our findings indicate that HFD can evoke earlier microgliosis and more detrimental neuronal death/loss in the somatosensory cortex after transient ischemia than ND evokes.